Oddziaływanie na Candida albicans fotodynamicznych własności błękitu metylenowego w połączeniu z promieniowaniem laserowym o długości fali 630 nm – badanie in vitro - Pasyechnikova, Nataliya; Zborovskaya, Olexandra; Kustrin, Taras (Klinika Oczna / Acta Ophthalmologica Polonica, 2009)
The study had to define influence of combined applications of laser radiation and methylene blue (MB) on pathogenic culture of Candida albicans in vitro. The experimental study was done at standard techniques of method of cultivations in a broth. The laser irradiation of cultures was done at once after addition of MB in concentration 0.05%, 0.1% and 0.2%. During studying action of MB in dark, influence of MB to the growth of test-shtam without laser radiation, were prepared fluid Gissa’s broth with glucose without Andrede’s indicator. Activation of MB was done by laser with wave length 630 nm during 3 or 5 min. All experiments were passed in 4 parallels and 3 repeats. Maximal suppression of growth of microorganisms was noted in group with using 0.1% MB with laser radiation 3 minutes without centrifugation after 24 hours. Maximal suppression of growth was noted in group after centrifugation with 0.05% MB with exposure of laser 3 min. after 48 hours. Sensitivity of pathogenic culture of Candida albicans to application of МB and laser raises accordingly to increase of concentration of MB.